Intervensi Menghilangkan Stigma dan Diskriminasi Kusta di Puskesmas Pauh Kamba, Padang Pariaman - Tutty Ariani; Rina Gustia; Satya Wydya Yenny; Qaira Anum; Gardenia Akhyar; Ennesta Asri; Irdawati Izrul; Yenni Raflis; Rizkia Chairani Asri; Mardhiati Mardhiati; Riri Prima Yolanda (Warta Pengabdian Andalas, 2022)
The increase in new leprosy cases in the year 2021 spread across 19 regencies, with the highest distribution in Padang Pariaman, and it is still a problem in West Sumatera Province. Based on this condition, "the pockets of leprosy" has been created, which play a role in the transmission of leprosy, so the elimination effort experiences difficult. Public Health Center of Pauh Kamba in Padang Pariaman Regency has 12 (19%) new multibacillary cases. In commemoration of World Leprosy Day in the year 2022, Indonesian Society of Dermatology And Venereology (INSDV/Perdoski), Indonesian Physical Medicine and Rehabilitation Association (Perdosri), and Padang Pariaman District Health Office have been struggling to break the chain of transmission of leprosy by increasing understanding of leprosy, self-care of leprosy, prevention of disability, and revitalize the activities of self-care groups by local health workers.